Strategi Pengembangan Kampung Warna-Warni Teluk Seribu Balikpapan Berdasarkan Sapta Pesona Dalam Meningkatkan Kunjungan Wisatawan - Alifa, Irvisya; Nugroho, Rizky Arif; Syafitri, Elin Diyah; Dewanti, Ajeng Nugrahaning (COMPACT: Spatial Development Journal, 2024)
Based on RTRW and RPJMD of Balikpapan City, one of the tourism objects that becomes the focus of tourism development is Kampung Warna-Warni Teluk Seribu Balikpapan. Sapta Pesona is a benchmark element for improving the quality of tourism products consisting of seven elements, namely, Security, Order, Cleanliness, Coolness, Beauty, Friendliness, and Memories. The use of the concept of Sapta Pesona is expected to provide knowledge to tourists and the surrounding community to be more aware of tourism and develop new attractions for tourists of Kampung Warna-Warni Teluk Seribu so that it becomes sustainable tourism. Thus, the purpose of this research is to formulate the development strategy of Kampung Warna-Warni Teluk Seribu Balikpapan based on Sapta Pesona in increasing tourist visits. In order to achieve that goal, the development strategy of Kampung Warna-Warni Teluk Seribu Balikpapan based on Sapta Pesona is formulated by comparative analysis to 6 sub-variables that become development priorities, namely Provision of Security & Safety Information, Provision of Security System, Order Regulation, Cleanliness Management, Beauty of Tourist Location, and Memories of Tourist Attraction. The formulation of this development strategy is carried out by comparing existing conditions with Best Practice related to each sub variable.